Experimental and numerical evaluation of novel dual-channel windcatchers for energy-saving technology integrations - Li, Jiaxiang (2024)
Windcatchers are utilized in building design as natural ventilation devices, providing fresh air supply and thermal comfort under suitable outdoor conditions. However, their performance is often constrained by environmental factors such as outdoor temperature, wind speed and direction. While passive heating, cooling, and heat recovery devices have been integrated into conventional windcatcher designs, the impact of changing wind conditions, which can render the windcatcher ineffective, is often not considered. Addressing this gap, this research builds upon two novel dual-channel windcatcher systems to provide a fresh air supply irrespective of the wind direction and allow for passive/low-energy technology integration. The first proposed design is a rotary scoop windcatcher consisting of a rotary wind scoop and a chimney. In this design, the positions of the supply and return duct are “fixed” or would not change under changing wind directions to ensure a consistent fresh air supply, irrespective of wind direction and facilitate the integration of passive/low-energy technologies. An open wind tunnel and test room were employed to experimentally evaluate the ventilation performance of the proposed windcatcher prototype. A Computational Fluid Dynamic (CFD) model was developed and validated to further evaluate the system's ventilation performance. The results confirmed that the system could supply sufficient fresh air and exhaust stale air under changing wind directions. The validated CFD model was enhanced in the simulations, incorporating technologies such as an anti-short-circuit device, wing walls, wind scoop area, and wind cowl design, to increase the pressure difference between the inlet and outlet and reduce the system friction. The modified windcatcher achieved a 28% improvement in ventilation rate and outperformed a conventional four-sided windcatcher of the same size by up to 58%. Furthermore, the full-scale simulations of the building and windcatcher of varying heights were conducted using an atmospheric boundary layer wind flow to better capture the true nature of the wind flow that the building will encounter in real-world conditions to provide a more realistic assessment of the windcatcher's performance. The second design is a windcatcher with inlet openings equipped with flap fins and a chimney in the middle. As this flap fins louver windcatcher is developed from the rotary scoop windcatcher, the dual-channel design remains for the fixed supply and return duct position for passive/low-energy technology integration. Inspired by the check valve device, the flap fin mechanism allows wind to flow only one way into the windcatcher's supply channel which creates a substitution for the wind scoop. The lightweight flap fin operates via gravity and takes advantage of the wind pressure around the openings to control the airflow. The wind tunnel experiment and CFD simulation model were developed to evaluate the ventilation performance of the proposed windcatcher prototype and investigate the impact of each parameter like the thickness, length, layout of the fins and wind directions. The field test of the flap fins louver windcatcher was also tested in this research. The results showed that the ventilation performance of the flap fin louver windcatcher was independent of the wind direction in the field test and wind tunnel experiment, and the use of lighter and longer fins would enhance the ventilation rate. The current scaled experiment model with a diameter of 20cm could provide about 10L/s fresh air supply at 2m/s environment wind speed with an air change rate over 27 h. Overall, this research contributes to the development of more efficient windcatcher systems for further passive technology integrations, enhancing their viability as sustainable ventilation solutions. Two novel windcatchers were proposed in this research and the ventilation performance of the windcatchers was independent of the environmental wind direction. Passive technologies such as passive heat recovery were integrated into the windcatchers to provide indoor thermal comfort. The ventilation efficiency of the two windcatchers was also higher than the traditional conventional windcatchers.